FYP Addiction and the Art of Digital Selling: A Study of MSMEs on TikTok Shop: Kecanduan FYP dan Seni Berdagang Digital: Studi tentang UMKM di TikTok Shop - Author, Muhammad Nailul (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to explore the experiences of micro, small, and medium enterprises (MSMEs) in utilizing TikTok Shop as a digital selling platform, particularly in their efforts to appear on the For You Page (FYP). Using a descriptive qualitative approach and phenomenological method, this research involves eight MSME actors who actively produce content and conduct live selling. The findings reveal that FYP is not only perceived as a visibility target but also as a source of social validation and psychological pressure. MSMEs develop content strategies based on trends, storytelling, and personalization while navigating the ambiguity between promotion and entertainment. Moreover, emotional stress is found to be a consequence of algorithmic demands for consistent performance. These findings highlight the importance of understanding FYP as a performative and emotional space within digital business strategies. This study suggests the need for ongoing support for MSMEs to maintain a balance between creativity and mental well-being in the platform-based digital economy.